Molecular Mechanisms of Mast Cell Activation by Cholesterol-Dependent Cytolysins - Draberova, Lubica; Tumova, Magda; Draber, Petr (Frontiers in Immunology, 2021)
Mast cells are potent immune sensors of the tissue microenvironment. Within seconds of activation, they release various preformed biologically active products and initiate the process of de novo synthesis of cytokines, chemokines, and other inflammatory mediators. This process is regulated at multiple levels. Besides the extensively studied IgE, IgG, toll-like, MRGPR, and other protein receptor signaling pathways, there is a critical activation pathway based on cholesterol-dependent, pore-forming cytolytic exotoxins produced by Gram-positive bacterial pathogens. This pathway is initiated by binding the exotoxins to plasma membrane cholesterol, followed by their dimerization, multimerization, pre-pore formation, and pore formation. At low sublytic concentrations, the exotoxins induce mast cell activation, including degranulation, calcium response, and transcriptional activation, resulting in production of cytokines and other inflammatory mediators. Higher toxin concentrations lead to cell death. Similar activation events are observed when mast cells are exposed to sublytic concentrations of saponins or some other compounds interfering with the membrane integrity. We review the molecular mechanisms of mast cell activation by pore-forming bacterial exotoxins and other compounds inducing cholesterol-dependent plasma membrane perturbations. We discuss the importance of these signaling pathways in innate and acquired immunity.